2007
DOI: 10.1038/cr.2007.47
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 regulates processing of NF-κB2 p100 involving protection of NF-κB-inducing kinase (NIK) from autophagy-mediated degradation

Abstract: NF-κB-inducing kinase (NIK) is required for NF-κB activation based on the processing of NF-κB2 p100. Here we report a novel mechanism of NIK regulation involving the chaperone 90 kDa heat shock protein (Hsp90) and autophagy. Functional inhibition of Hsp90 by the anti-tumor agent geldanamycin (GA) efficiently disrupts its interaction with NIK, resulting in NIK degradation and subsequent blockage of p100 processing. Surprisingly, GA-induced NIK degradation is mediated by autophagy, but largely independent of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 36 publications
6
88
0
Order By: Relevance
“…Evidence exists that in this ER-positive and selective estrogen modulator (one of which is tamoxifen)-sensitive cell lines, NF-B signaling should be attributed to p50 and Bcl3 rather than to p65 (68,69). Another interesting work demonstrated that autophagy represents a new route for NF-B-inducing kinase degradation and negatively regulates alternative NF-B pathways (47). In light of these findings and of our data, it is tempting to speculate that autophagy, once acutely induced through a classical mode of NF-B activation, could terminate the whole NF-B pathway, working as a negative feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists that in this ER-positive and selective estrogen modulator (one of which is tamoxifen)-sensitive cell lines, NF-B signaling should be attributed to p50 and Bcl3 rather than to p65 (68,69). Another interesting work demonstrated that autophagy represents a new route for NF-B-inducing kinase degradation and negatively regulates alternative NF-B pathways (47). In light of these findings and of our data, it is tempting to speculate that autophagy, once acutely induced through a classical mode of NF-B activation, could terminate the whole NF-B pathway, working as a negative feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, autophagic process has a negative impact on the activation of IKK and NF-B. For instance, autophagy facilitates the degradation of the IKK complex and its upstream activator NF-Binducing kinase, contributing to the inhibition of NF-B signaling (47). Furthermore, autophagic process depletes p62 (sequestosome1), an activator of the IKK complex, resulting in a diminished activity of NF-B (48).…”
Section: Discussionmentioning
confidence: 99%
“…35 In most cancer cells, the hyperactivation of HSP90 stabilizes its client proteins and protects from stress; the specific inhibition of HSP90 by some chemicals can lead to the degradation of its clients via autophagy. 36,37 In leukemic cells, sodium selenite decreased HSP90 expression and attenuated its interaction with the protein inhibitor of nuclear factor κB, finally resulting in the cell-signaling switch from autophagy to apoptosis. 9 Herein, we proved that HSP90 sequestered by SeNPs is the real cause of HSP90 decreases, therefore revealing the link between autophagy inhibition and HSP90 decrease in selenite-treated cancer cells.…”
Section: Endogenous Senps-inhibited Autophagymentioning
confidence: 99%